Determinants of Fraud Detection Ability Among Auditors - Tertiarto Wahyudi; Umi Kalsum; Rika Henda Safitri (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study aims to examine the influence of competence, independence, work experience, time pressure, and professional skepticism on auditors’ ability to detect fraud, particularly in the context of Public Accounting Firms in Southern Sumatra, Indonesia, where prior studies have shown inconsistent results. Design/methodology/approach – This research employs a quantitative approach using primary data collected through questionnaires distributed to auditors. A total of 64 auditors participated as respondents. The data were analyzed using multiple linear regression with SPSS software to test the proposed relationships between variables. Finding/Results – The results reveal that competence, independence, work experience, and professional skepticism have a positive and significant effect on auditors’ ability to detect fraud. However, time pressure does not have a significant effect on fraud detection ability. Originality/Value – This study contributes to the auditing literature by providing empirical evidence from an emerging economy, specifically Southern Sumatra, Indonesia. It emphasizes the critical role of professional competence, independence, and skepticism in enhancing auditors’ effectiveness in fraud detection, offering practical implications for improving audit quality in similar contexts.